Protection of humanity's cultural and historic heritage in space - Justin Walsh (Elsevier BV, 2012)
While the international community has acted forcefully since WorldWar II to protect sites and objects of cultural or historic significance on Earth, little attention has been paid to the same kinds of sites and objects in space. There are important ethical and scholarly reasons for wanting to preserve sites and in situ objects in off-Earth contexts from destruction or commercial exploitation. Innovative space research equipment, such as spacecraft, satellites, and space stations, and the locations of historic missions, such as Tranquility Base, therefore deserve formal international recognition and protection. Appropriate models for developing a comprehensive protective scheme can be found in existing international protocols, especially the 1959 Antarctic Treaty (and later additions), the 1970 UNESCO Convention on Cultural Property, the 1972 UNESCO World Heritage Convention, and the 2001 UNESCO Convention on the Underwater Cultural Heritage. In addition, space agencies and professional organizations can mandate adequate and ethical planning for the post-operational phases of space missions to include arrangements for heritage protection.